The Official Guide for GMAT Quantitative Review 2016 (Wiley, 2015)
Ace the GMAT® with the only official study guides from the creators of the exam With 25% brand new content, The Official Guide for the GMAT Quantitative Review 2016 is the only official study guide focusing on the quantitative portion of the GMAT® exam. It delivers more than 300 retired questions from the GMAT®, complete with answer explanations, to help focus your test preparation efforts. Also includes exclusive online resources: Build your own practice tests with exclusive online access to 300 problem solving and data sufficiency questions from official GMAT exams Exclusive access